Tindak Pidana Pencurian Dengan Pemberatan (Studi Pada Putusan Nomor 398/Pid.B/2022/PN.Amb) - Paul Edward Mataheru; Yanti Amelia Lewerissa; Steven Makaruku (Faculty of Law Universitas Pattimura, 2023)
The element of joint theft is defined as an act committed jointly, with the same intention as stipulated in Article 56 of the Criminal Code, namely participation in the act. Participation in committing is defined as